Hinfinity control under asymptotic tracking constraint and nonproper output weights - Yagoubi, Mohamed; Feng, Yu; Huang, Yanyu (International journal of control, 2019)
This paper presents a complete solution to the measurement output feedback H∞control problem subject to asymptotic tracking of an infinite energy reference andthe presence of nonproper output weights. Relying on generalized Sylvester-typeequations, a set of all stabilizing controllers is characterized, explicitly exhibitingthe impacts of the reference signal and the output weight on the resulting con-trollers. Based on this specific parameterization, additional disturbance attenuationis tackled, and both full-order and reduced-order controller synthese are discussed. Itis observed that the multiobjective problem is equivalent to a standard problem foran axillary system constructed from the original weighted system with the controlinput matrix and measurement output matrix being augmented by solutions to gen-eralized Sylvester-type equations. An example is included to show the effectivenessof the present results.